Investigating the Relationship Between Youth Leaders’ Lifelong Learning Dispositions and Job Satisfaction - BALIKCI, Murat; YAVUZ EROGLU, Sultan (International Journal of Holistic Health, Sports and Recreation, 2024)
The aim of this study is to examine the job satisfaction and lifelong learning tendencies of youth leaders in terms of some variables. The study group of the research consists of 301 volunteer participants from youth leaders working in the General Directorate of Youth Services of the central organization of the Ministry of Youth and Sports and youth leaders working in youth centers in the provincial organizations of the Ministry in 81 provinces and their districts. Personal Information Form, Minnesota Job Satisfaction Scale and Lifelong Learning Disposition Scale were used as data collection tools. Independent Groups T-Test, One-Way Analysis of Variance and Correlation Analysis were used to evaluate the data. According to the findings of the study, job satisfaction sub-dimension averages and total score did not show a significant difference according to gender and graduation status variables (p>0.05), but a significant difference was found according to age and years of service variables (p<0.05). Lifelong learning sub-dimension averages and total score did not show a significant difference according to gender, age and graduation status variables (p>0.05), but a significant difference was found according to years of service variable (p>0.05). A low level positive significant relationship was found between job satisfaction total score and lifelong learning total score. In line with these results, it can be said that as internal satisfaction increases, openness to development and willingness to learn will increase.